Estimation of Hazard Cumulative Function Using the Nelson-Aalen Method on Covid-19 Patient Data in Jember Regency - Ramadhani, Hilvania; Pauziah, Rini (Indonesian Council of Premier Statistical Science, 2025)
The Covid-19 pandemic presents a major challenge in the health sector, especially related to understanding patient recovery patterns. This study aims to estimate the cumulative hazard function using the Nelson-Aalen method on the length of treatment data of Covid-19 patients who have recovered in Jember Regency. The Nelson-Aalen method is a non-parametric approach that does not require certain distribution assumptions and is suitable for survival data, especially those subjected to right censorship. In this study, all patient data was complete without sensors. The analysis was performed with R software, resulting in a cumulative hazard curve that showed an increased risk of recovery as the treatment time increased. The results of this study provide an empirical picture of patient recovery patterns and serve as a basis for evaluating health service efficiency and hospital capacity planning during the pandemic. In addition, the application of the Nelson-Aalen method reinforces the contribution of non-parametric statistical methods in epidemiological studies